Push-Pull Heterocyclic Dyes Based on Pyrrole and Thiophene: Synthesis and Evaluation of Their Optical, Redox and Photovoltaic Properties - Sara Fernandes (2022)
Three heterocyclic dyes were synthesized having in mind the changes in the photovoltaic, optical and redox properties by functionalization of 5-aryl-thieno[3,2-b]thiophene, 5-arylthiophene and bis-methylpyrrolylthiophene π-bridges with different donor, acceptor/anchoring groups. Kno-evenagel condensation of the aldehyde precursors with 2-cyanoacetic acid was used to prepare the donor-acceptor functionalized heterocyclic molecules. These organic metal-free dyes are con-stituted by thieno[3,2-b]thiophene, arylthiophene, bis-methylpyrrolylthiophene, spacers and one or two cyanoacetic acid acceptor groups and different electron donor groups (alkoxyl, and pyrrole electron-rich heterocycle). The evaluation of the redox, optical and photovoltaic properties of these compounds indicate that 5-aryl-thieno[3,2-b]thiophene-based dye functionalized with an ethoxyl electron donor and a cyanoacetic acid electron acceptor group/anchoring moiety displays as sensitizer for DSSCs the best conversion efficiency (2.21%). It is mainly assigned to the higher molar extinction coefficient, long π-conjugation of the heterocyclic system, higher oxidation potential and strong electron donating capacity of the ethoxyl group compared to the pirrolyl moiety.